(untitled) (Revista de Estudos da Linguagem, 2007)
A number of recent works has shown that linguistic representationsincorporate redundant information which plays an important role inlinguistic systems. Works on experimental phonetics and along thelines of Laboratory Phonology indicate the gradual nature of phoneticrepresentations (BROWMAN; GOLDSTEIN, 1992; ZSIGA, 1995;ALBANO, 2001; BYBEE, 2001, 2002; PIERREHUMBERT, 2001).This paper follows this line of research by investigating plural loss inBrazilian Portuguese. We will investigate lenition in BrazilianPortuguese plural forms that end in a sibilant, as in mês ‘month’whose plural form is meses ‘months’. This paper offers evidencefor the gradual implementation of phonetic changes by showing thatthe loss of a morphological category (plural) leaves traces in thecontinuum of speech in the form of compensatory lengthening.